First insights into the population characteristics and seasonal occurrence of the great hammerhead shark, Sphyrna mokarran (Rüppell, 1837) in the Western Tuamotu archipelago, French Polynesia - Boube, Tatiana; Azam, Claire-Sophie; Guilbert, Antonin; Huveneers, Charlie; Papastamatiou, Yannis P.; Mourier, Johann; Trujillo, José E.; Femmami, Nastazia; Kunovsky, Andréa; Bersani, Florent; Laurent, Enzo; Bousseyroux, Alice; et al. (Frontiers in Marine Science, 2023)
The occurrence and seasonality of the Critically Endangered great hammerhead shark, Sphyrna mokarran, is data deficient in the Central Pacific region. Using photo-identification and laser-photogrammetry, we describe the seasonal population of great hammerhead sharks in the Tiputa pass (Rangiroa atoll) and Tuheiava pass (Tikehau atoll) in the Tuamotu archipelago of French Polynesia. During the austral summer of 2020 and 2021, we recorded a female-biased aggregation of at least 55 individuals (54 females; 1 unknown sex), representing an unprecedented number of S. mokarran in one study. All measured sharks were likely mature with pre-caudal lengths ranging from 147 cm to 297 cm (n = 35). Videos from citizen scientists recorded over a 15-year period enable us to identify 30 additional individuals between 2006 and 2019, with strong evidence of sexual segregation during the year. Our findings revealed seasonal residency (n = 32) of up to 6 days/month and for up to 5 months at the study site during the austral summer. We also demonstrated site fidelity with 32 individuals returning to the same atoll for up to 12 years between the first and last sighting, and with limited evidence of connectivity between the two sites. Our analysis also provides preliminary insight into the environmental factors driving S. mokarran aggregation in the Tiputa pass, suggesting a marked influence of the lunar cycle and of ocellated eagle rays (Aetobatus ocellatus) abundance. This study, conducted in situ with non-invasive methods offers a unique opportunity to study a great hammerhead shark population in a near-pristine ecosystem and provides important life-history elements for the Central Pacific region.